A Computational Study On Structural Behaviour Of Surfaces With Curved Fold Lines - Khor, Yong Yee (Universiti Sains Malaysia, 2021)
Surface with curved creases derived from origami can be advantageous in roof structures which can improve strength while preserving the aesthetic values. However, there is still a great deal of ambiguity and insufficient research on the potential use of curved fold lines. This study targets to formulate a systematic computational method for the generation of surface with curved creases with different factors governing the surface configuration. This study also aims to investigate the effects of pattern of curved crease folds, thickness of surface and the change of the rise-span ratio on structural behaviour of surface with curved crease in terms of load-carrying capacity and stiffness. Several criteria had been established for the selection of origami with curved creases based on the extensive collection by the previous researcher. The outcome shows three origami models have potential application in roofing systems, namely Non-inflated Degree-4 Vertices, Four Circular Mountain Ridge Curves and Four Elliptical Mountain Ridge Curves. Image Capturing Method (ICM) is adopted to develop the outlines of the origami models and the elevation profiles from the raster 3-D paper forms. Surface formation is then proceeded before the finite element analysis. These origami models are then scaled with 100 and assigned with additional analytical properties to evaluate the structural performance. Finite element analysis under self-weight condition only is carried out corresponding to the adjustments, i.e., elevation profiles of curved fold lines, overall risespan ratio and surface thickness. The best-performing model in terms of better stress distribution and lower displacement with the consideration of self-weight is then selected. The results obtained from the variation of elevation profiles of curved fold lines show that all models under the category of Model 01 (Non-inflated Degree-4 Vertices) and Model 02 (Four Circular Mountain Ridge Curves) failed to meet the tensile stress limit. Comparing these two types of models, Model 01 shows relatively higher stress and displacement. In contrast, only the models under category of Model 03 satisfy the stress limit. This is mainly due to the geometry patterns of the origami models which lead to different stress distributions over the surfaces. For the rest of the modifications, the FE results show that all models under the category Model 03 are still within the allowable stress and deflection limits with slight variation. Therefore, the presence of curved fold lines and the greater overall effective depth of the structure help to enhance the performance in load-carrying capacity.